2015
DOI: 10.1590/1519-6984.00114
|View full text |Cite
|
Sign up to set email alerts
|

Community ecology of the metazoan parasites of Brazilian sardinella, Sardinella brasiliensis (Steindachner, 1879) (Actinopterygii: Clupeidae) from the coastal zone of the State of Rio de Janeiro, Brazil

Abstract: Between March 2010 and August 2011 were necropsied 100 specimens of Sardinella brasiliensis (Steindachner, 1879), from the coast of the State of Rio de Janeiro, Brazil (22°51'S, 43°56'W), to study their community of metazoan parasites. All specimens of S. brasiliensis were parasitized by at least one species of metazoan parasite, with mean of 68.7 ± 71.2 parasites/fish. Eleven species were collected: 3 digeneans, 1 monogenean, 2 cestodes, 3 nematodes and 2 copepods. The digenean Myosaccium ecaude Montgomery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
4
11
1
Order By: Relevance
“…The parasitic indices for C . gracilis in the present study were higher then those of Moreira et al [ 14 ], who reported a prevalence of 15%, mean intensity of 1.1 ± 0.3 and mean abundance of 0.3. However, the site of infection, the body cavity, reported by Moreira et al [ 14 ] differed from that of the present study which represents the first report of this parasite in the musculature of S .…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…The parasitic indices for C . gracilis in the present study were higher then those of Moreira et al [ 14 ], who reported a prevalence of 15%, mean intensity of 1.1 ± 0.3 and mean abundance of 0.3. However, the site of infection, the body cavity, reported by Moreira et al [ 14 ] differed from that of the present study which represents the first report of this parasite in the musculature of S .…”
Section: Discussioncontrasting
confidence: 87%
“…Callitetrarhynchus gracilis was previously reported parasitizing S . brasiliensis off the coast of the state of Rio de Janeiro by Moreira et al [ 14 ]. However, these authors did not provide morphometric data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several authors have reported the presence of these parasites in marine fish, generally in greater prevalences in comparison with other helminths (São Clemente et al, 1994;Luque, 2004;Knoff et al, 2007Knoff et al, , 2013Barros, 2012). Anisakid larvae have been reported by several authors in species of fish of economic importance such as: Anchoa tricolor, Netuma barba, Brevoortia aurea, Pagrus pagrus, Prionotus punctatus, Genypterus brasiliensis, Aluterus monoceros, Paralichthysis isoceles, Rhamdia quellen, Lophius gastrophysus, Lutjanus analis, Sardinella brasiliensis, and Selene setapinnis (Palm, 1997;São Clemente et al, 1994;Cordeiro and Luque, 2004;Bicudo et al, 2005;Knoff et al, 2007;Saad and Luque, 2009;Dias et al, 2010;Felizardo et al, 2009;La Rue et al, 2010;Saad et al, 2012;Knoff et al, 2013;Hermida et al, 2014;Moreira et al, 2015;Fontenelle et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, studies regarding the metazoan parasite community of clupeids have been performed by Luque et al (2000), on the parasitic fauna of Harengula clupeola (Cuvier), by on Brevoortia aurea (Spix and Agassiz) and more recently by Moreira et al (2015) on Sardinella brasiliensis (Steindachner), all of them from the coastal zone of the State of Rio de Janeiro. However, despite being one of the most important species in artisanal fishing in Brazil, studies on the parasitic fauna of O. oglinum are still incipient.…”
Section: Introductionmentioning
confidence: 99%